Self Control Correlation With Academic Procrastination Among Vocational Students: Korelasi Pengendalian Diri dengan Penundaan Akademik di Kalangan Siswa Kejuruan - Reza Nur Aini; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic procrastination is a common behavioral issue that disrupts students’ learning performance and task completion in secondary education. Specific Background: Students in vocational schools frequently face simultaneous academic and practical demands that require strong self-regulation skills. Knowledge Gap: Empirical evidence focusing on the association between self-control and procrastination within vocational high school contexts remains limited. Aims: This study investigates the relationship between self-control and academic procrastination among students of SMK Informatika Sumber Ilmu. Results: Using a quantitative correlational design with 203 participants selected through proportionate stratified random sampling, data collected via validated Likert scales revealed a significant negative correlation (r = −0.623, p < 0.05), with self-control contributing 46.4% of variance in procrastination levels. Most students demonstrated moderate levels on both variables. Novelty: The study provides context-specific evidence from vocational education, highlighting behavioral regulation patterns in students preparing for both academic and workplace demands. Implications: Strengthening self-regulatory skills may reduce delaying behaviors and support more disciplined academic performance, offering practical direction for school-based interventions and counseling programs. Keywords: Academic Procrastination, Self Control, Vocational Students, Correlational Study, Student Behavior Key Findings Highlights Strong inverse association between regulation capacity and delay tendencies Nearly half of behavioral variance explained by internal regulation factor Majority of participants categorized within moderate behavioral levels